Fluid and carbohydrate replacement during intermittent exercise - Shi, X.; Gisolfi, C. V. (Sports Medicine, 1998)
Most studies relating to fluid replacement have addressed the problem of drinking during prolonged exercise. Fluid replacement is also very important for intermittent exercise, although it has not been extensively studied. More studies in this area would help coaches and athletes understand the importance of fluid balance and carbohydrate supplementation during intermittent exercise. Based on available data, it can be concluded that: (i) because of high exercise intensity, sweat loss and glycogen depletion during intermittent exercise are at least comparable with those during continuous exercise for a similar period of time. Therefore, the need to ingest a sport drink or replacement beverage during intermittent exercise may be greater than that during continuous exercise in order to maintain a high level of performance and to help prevent the possibility of thermal injury when such activity occurs in a warm environment; (ii) the volume of ingested fluid is critical for both rapid gastric emptying and complete rehydration; and (iii) osmolality (250 to 370 mOsm/kg), carbohydrate concentration (5 to 7%), and carbohydrate type (multiple transportable carbohydrates) should be considered when choosing an effective beverage for rehydration and carbohydrate supplementation during intermittent exercise.